A model for community-driven development of best practices: the Ocean Observatories Initiative Biogeochemical Sensor Data Best Practices and User Guide - Hilary I. Palevsky; Sophie Clayton; Heather Benway; Mairead Maheigan; Dariia Atamanchuk; Roman Battisti; Jennifer Batryn; Annie Bourbonnais; Ellen M. Briggs; Filipa Carvalho; Alison P. Chase; Rachel Eveleth; et al. (Frontiers in Marine Science, 2024)
The field of oceanography is transitioning from data-poor to data-rich, thanks in part to increased deployment of in-situ platforms and sensors, such as those that instrument the US-funded Ocean Observatories Initiative (OOI). However, generating science-ready data products from these sensors, particularly those making biogeochemical measurements, often requires extensive end-user calibration and validation procedures, which can present a significant barrier. Openly available community-developed and -vetted Best Practices contribute to overcoming such barriers, but collaboratively developing user-friendly Best Practices can be challenging. Here we describe the process undertaken by the NSF-funded OOI Biogeochemical Sensor Data Working Group to develop Best Practices for creating science-ready biogeochemical data products from OOI data, culminating in the publication of the GOOS-endorsed OOI Biogeochemical Sensor Data Best Practices and User Guide. For Best Practices related to ocean observatories, engaging observatory staff is crucial, but having a “user-defined” process ensures the final product addresses user needs. Our process prioritized bringing together a diverse team and creating an inclusive environment where all participants could effectively contribute. Incorporating the perspectives of a wide range of experts and prospective end users through an iterative review process that included “Beta Testers’’ enabled us to produce a final product that combines technical information with a user-friendly structure that illustrates data analysis pipelines via flowcharts and worked examples accompanied by pseudo-code. Our process and its impact on improving the accessibility and utility of the end product provides a roadmap for other groups undertaking similar community-driven activities to develop and disseminate new Ocean Best Practices.

Airway Exposure to Modified Multi-walled Carbon Nanotubes Perturbs Cardiovascular Adenosinergic Signaling in Mice - Leslie C. Thompson; Nicole L. Sheehan; Dianne M. Walters; Robert M. Lust; Jared M. Brown; Christopher J. Wingard (Cardiovascular Toxicology, 2019)

Better Regional Ocean Observing Through Cross-National Cooperation: A Case Study From the Northeast Pacific - John A. Barth; Susan E. Allen; Edward P. Dever; Richard K. Dewey; Wiley Evans; Richard A. Feely; Jennifer L. Fisher; Jonathan P. Fram; Burke Hales; Debby Ianson; Jennifer Jackson; Kim Juniper; et al. (Frontiers in Marine Science, 2019)

Ultrafine Particulate Matter Increases Cardiac Ischemia/Reperfusion Injury via Mitochondrial Permeability Transition Pore - Nathan A. Holland; Chad R. Fraiser; Ruben C. Sloan; Robert B. Devlin; David A. Brown; Christopher J. Wingard (Cardiovascular Toxicology, 2017)

Serum 25-hydroxyvitamin D and breast cancer in the military: a case–control study utilizing pre-diagnostic serum - Sharif B. Mohr; Edward D. Gorham; John E. Alcaraz; Christopher I. Kane; Caroline A. Macera; J. Kellogg Parsons; Deborah L. Wingard; Ronald Horst; Cedric F. Garland (Cancer Causes & Control, 2013)

Edge gradients provide evidence of ecological interactions in planktonic thin layers - Kelly J. Benoit-Bird; Timothy J. Cowles; Christopher E. Wingard (Limnology and Oceanography, 2009)
Physical, optical, and acoustical data from Monterey Bay, California, USA, describing the distributions of phytoplankton, zooplankton, and small fish as well as gradients in the physical habitat were used to examine the interactions between vertically compressed plankton structures (thin layers), their consumers, and the local physical forces they experience. The relationship between upper and lower edge gradients of a layer were used to define layer ‘shape'. The steepness of the vertical gradient on the top vs. the bottom of the plankton layer was correlated to the difference in the relative abundance of consumers above and below the layer. Phytoplankton layer gradients were steeper when more zooplankton were present on one side of the layer vs. the other while zooplankton layers were more diffuse when a greater number of fish were adjacent to one side of the layer than the other. Both layer types showed nearly symmetrical gradients when predators were in low abundance or absent. Predator‐associated differences in phytoplankton and zooplankton layer shape were not correlated with vertical gradients in shear or mixing potential surrounding layers. In the absence of strong physical gradients, grazers can play an important role in structuring plankton thin layers. These observations likely represent one end of a continuum of biological and physical forcing responsible for formation and maintenance of thin plankton layers.

Epsilon protein kinase C lengthens the quiescent period between spontaneous contractions in rat ventricular cardiac myocytes and trabecula - Mourad Ogbi; Christopher J. Wingard; Safia Ogbi; John A. Johnson (Naunyn-Schmiedeberg's Archives of Pharmacology, 2004)

Cardiac neural crest ablation alters aortic smooth muscle force and voltage-sensitive Ca2+ responses - Christopher J. Wingard; Robert E. Godt (Journal of Muscle Research and Cell Motility, 2002)